Audrey Hepburn : A Little Golden Book Biography - Easton, Emily; Surrey, Ellen (New York : A GOLDEN BOOK, 2024)
c
Keywords: Hepburn, Audrey, -- 1929-1993; Motion picture actors and actresses -- United States- -- Biography -- Juvenile literature; Actresses -- Biography -- Juvenile literature; Biographies